Epidemiological survey of Rheumatic fever, Rheumatic heart disease and Congenital heart disease among school children in Kathmandu valley of Nepal - Prajapati, Dipanker; Sharma, Deewakar; Regmi, Prakash Raj; Khanal, Harihar; Baidya, Sajan Gopal; Rajbhandari, Sujeeb; Rokka, Madhu; Singh, Sarju Raj; Shrestha, Anmol; Shrestha, Abha; Belbase, Rupesh Jung; Sulpya, Sambridhi (Nepalese Heart Journal, 2014)
Background and Aims: Rheumatic Fever, Rheumatic Heart Disease and Congenital Heart disease are the most common cardiac problems in school children. Prior studies have reported different prevalence rate of Rheumatic Heart Disease among different groups of population of Nepal. The aim of this study was to estimate the prevalence of Rheumatic Fever, Rheumatic Heart Disease and Congenital Heart Disease among school children in Kathmandu Valley of Nepal. Methods: Cardiac screening of 34,876 school children from 115 randomly selected public schools from two cities of Kathmandu Valley (Kathmandu and Lalitpur) was done. Cases with abnormal findings in auscultation underwent echocardiography and the diagnosis was confirmed. Results: The prevalence of Congenital Heart Disease was noted to be 1 per thousand and prevalence of Rheumatic Heart Disease was found to be 0.90 per thousand (in the age group 5-16 years) with the most common lesion being Mitral Regurgitation. No significant statistical difference was noted between male and female students in both the cases of Rheumatic Heart Disease and Congenital Heart Disease. No cases of Acute Rheumatic Fever were noted. Conclusion: The prevalence of Rheumatic Heart Disease among school children in Kathmandu valley was noted to be lower than reported in similar previous studies. Primary and secondary prevention programs of RF/RHD have been effective in Nepal and are needed to be strengthened and expanded to further reduce the burden of these diseases. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 1-5 DOI: http://dx.doi.org/10.3126/njh.v10i1.9738